Allied armies in Sicily and Italy, 1943-1945 : photographs from Wartime Archives - Forty, Simon (Images of war., 2019)
A pictorial history of Allied forces making their way through Italy in the final years of World War II, featuring rare photos from wartime archives. The Italian campaign was one of the most debated of World War II, splitting the American and British allies, and causing great disharmony. After the fall of Rome and the surrender of Italy, the invasion of Normandy led to the Italian campaign becoming a sideshow as the "D-Day Dodgers" fought their way through Italy to the Alps against a grinding defense and extreme weather. In a sequence of 200 wartime photographs Simon Forty sums up the major events of the conflict--from the landings on Sicily to the crossing of the Po. Commanded first by Sir Harold Alexander and then Mark Clark, the Allied armies (U.S. Fifth and British Eighth) drew men not only from Britain, the United States, France, and Poland, but also from all over the Commonwealth--from Australia, Canada, India, New Zealand and South Africa--as well as such other countries as Brazil, Czechoslovakia, Greece, and Palestine. The devastation caused by the war in the cities, towns, and countryside is part of the story, but perhaps the most powerful impression is made by the faces of the soldiers themselves as they look out from the Italian front of so long ago. "Another addition to the very popular Images of War series, with a mass of outstanding and rare images. The author covers campaigns in Sicily and Italy as the Allies slogged their way north, using amphibious and airborne assault to bypass the German lines--Very Highly Recommended." --Firetrench